If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3y+6=6-5y
We move all terms to the left:
3y+6-(6-5y)=0
We add all the numbers together, and all the variables
3y-(-5y+6)+6=0
We get rid of parentheses
3y+5y-6+6=0
We add all the numbers together, and all the variables
8y=0
y=0/8
y=0
| 30=0.24x+6 | | (6x)+((6x)/10)=624 | | 800A+1200R=1,000,000=r | | 39=3(8+p) | | 5m+12=-31 | | (4x+7)+(2x+5)=90 | | 3x÷x-1=0 | | 1.5=1.25x | | 4(k+6)=-(-6+5k) | | x2+10=-1 | | 26=4z-16 | | 16j-3j-10j=18 | | c+4/5=⅘ | | v+(-17)=-13 | | -5a-(1-5a)=39+5a | | 1/8+c=4/5-5(3) | | p-1/4⋅3=−5/6 | | (50+0.4x)+0.18(50+0.4x)=x | | b-2=16 | | (1/3x-11)=5 | | y/0.5=19 | | x=-73/4 | | (1/3x-11)^1/2=5 | | x=-3/4(26) | | 4=6-(x-5) | | x=-3/4x26 | | 6(8x-3)+3=3(8+3x) | | 8+3n/12=13+1/12n | | -¾=x/26 | | 8=4-2(x-5) | | 5x+2x-1=3x+9 | | 3+2r=3r+6r+1 |